Elevated Lactate by High-Intensity Interval Training Regulates the Hippocampal BDNF Expression and the Mitochondrial Quality Control System - Hu, Jingyun; Cai, Ming; Shang, Qinghui; Li, Zhaorun; Feng, Yu; Liu, Beibei; Xue, Xiangli; Lou, Shujie (Frontiers in Physiology, 2021)
Abstract High-intensity interval training (HIIT) is reported to be beneficial to brain-derived neurotrophic factor (BDNF) biosynthesis. A key element in this may be the existence of lactate, the most obvious metabolic product of exercise. In vivo, this study investigated the effects of a 6-week HIIT on the peripheral and central lactate changes, mitochondrial quality control system, mitochondrial function and BDNF expression in mouse hippocampus. In vitro, primary cultured mice hippocampal cells were used to investigate the role and the underlying mechanisms of lactate in promoting mitochondrial function during HIIT. In vivo studies, we firstly reported that HIIT can potentiate mitochondrial function (boost some of the mitochondrial oxidative phosphorylation (OXPHOS) genes expression and ATP production), stimulate BDNF expression in mouse hippocampus along with regulating the mitochondrial quality control system in terms of promoting mitochondrial fusion and biogenesis, and suppressing mitochondrial fission. In parallel to this, the peripheral and central lactate levels elevated immediately after the training. In vitro study, our results revealed that lactate was in charge of regulating mitochondrial quality control system for mitochondrial function and thus may contribute to BDNF expression. In conclusion, our study provided the mitochondrial mechanisms of HIIT enhancing brain function, and that lactate itself can mediate the HIIT effect on mitochondrial quality control system in the hippocampus.